Webinar Tentang Communication Skills and Career Guidance Graduation di SMK Negeri 1 ALIAN Kebumen - Dani Rizana; Ika Neni Kristanti (Politeknik Negeri Cilacap, 2021)
Vocational or vocational education is an education that is different from general education. Vocational education is directed at forming graduates who have professional insight, which is something that is embedded in a person that influences his behavior, namely caring for quality (not just so), working quickly, precisely, and efficiently without or with the supervision of others, respecting time, and maintain reputation. The purpose of implementing Career Guidance in Schools is so that students can: (increase their knowledge of themselves (self-concept); increase their knowledge of the world of work; develop their attitudes and values in dealing with job choices in preparation for entering them; improve thinking skills so that they can make decisions. about positions that suit him and are available in the world of work, and master basic skills that are important in work, especially the ability to communicate, cooperate and take initiative. This service activity is carried out for 1 day using several methods, including lectures and questions and answers. This community service activity is to provide communication skills to participants as a provision for preparation for graduation so that participants develop their attitudes and values in facing employment choices or the choice of continuing to a higher level of education. The impact of this service activity provides participants with knowledge and skills about communication skills and career guidance so that participants are better prepared to choose work or continue to a higher level after graduating from school.